Endodontic Orthograde Retreatments: Challenges and Solutions - Zanza A; Reda R; Testarelli L (Clinical, Cosmetic and Investigational Dentistry, 2023)
Alessio Zanza, Rodolfo Reda, Luca Testarelli Department of Oral and Maxillo-Facial Sciences, Sapienza University of Rome, Rome, ItalyCorrespondence: Rodolfo Reda, Department of Oral and Maxillo-Facial Sciences, Sapienza University of Rome, Via Caserta 06, Rome, 00161, Italy, Email rodolfo.reda@uniroma1.itAbstract: Endodontic orthograde retreatments are considered one of the possible treatment options in case of post-treatment diseases considering the promising results present in the literature. Despite this, a plethora of articles have been published on this topic, and drawing conclusions could be challenging. For this reason, this review aims to summarize the crucial points on each aspect of non-surgical endodontic retreatments, discussing and comparing the current protocols, techniques, materials, and indications. Taking into consideration data from the literature, in terms of diagnosis, CBCT should be considered the first choice, since it can thoroughly affect the diagnosis and treatment plan. Regarding the procedural phases, some conclusions can be drawn: when present, coronal restoration materials such as crowns, partial prostheses, post, and core should be removed; the use of magnification devices, ultrasonic instruments, and an in-depth interpretation of radiographic images with both 2D and 3D images are strongly recommended during the orifice location; additional protocols such as irrigants activation, ultrasonic cleaning, and rotary or reciprocating instrumentation of treated canals are strongly recommended for filling materials removal and to achieve a high-quality chemo-mechanical disinfection; perforations should be treated as soon as possible, and the material of choice to treat them is the MTA or other calcium-silicate-based repair materials; the presence of ledges does not intrinsically reduce the success rate of RCRts if properly managed; in case of instrument fragments, their removal should be considered as the first treatment option, however many variables should be considered to select the proper technique or consider the option of bypassing.Keywords: endodontic retreatment, endodontic retreatment outcome, diagnosis, ledge, perforation, instrument fragment removal, missed anatomy, filling material removal